Biomechanical advantage of low lateral hinge location in medial closing wedge distal femoral osteotomies. - Danieal Bin Ahmad (Nanyang Technological University, 2024)
The medial closing-wedge distal femoral osteotomy (MCDFO) is an established medical procedure used to manage lateral compartment cartilage injuries, knee osteoarthritis (OA), and genu valgum (knock-knee). However, there is a high incidence of lateral hinge fracture (LHF) after MCDFO, resulting in complications and loss of correction. The hypothesis proposes that placing the hinge point lower, specifically beneath the metaphyseal flare can safeguard the hinge against lateral hinge fracture, because of the metaphyseal bone's properties. The objective of this study is to use finite element analysis on femur bone model with differing hinge point locations and compare the results of maximum reaction forces, stiffness and area of maximum stress distribution around the hinge point. A finite element analysis was performed on a truncated femur bone model with differing hinge point locations in increments of 10 mm starting from the lowest hinge possible. A singular planar MCDFO was carried out at all the hinge points. A 10 mm remote displacement load is applied from the bottom to simulate closing the wedge. The bone properties used remained constant throughout the models for all hinge points. Comparing all 5 hinge points, the low hinge point and 10 mm above the low hinge was able to sustain the simulation without fracture. The remaining bone models fractured before the wedge was fully closed. The reaction forces and stiffness increased with increasing hinge points. The maximum stress distribution around the hinge point showed an increased in area with increasing hinge points with the exception of the high hinge model. This study found a trend suggesting the femur bone with MCDFO becomes more likely to fracture with increasing hinge points suggesting that the lower hinge points should be considered when conducting MCDFO as LHF are more likely to occur with incrementing hinge points.